A Novel Aptamer LL4A Specifically Targets Vemurafenib-Resistant Melanoma through Binding to the CD63 Protein - Hui Li; Juan Liu; Xiaojuan Xiao; Shuming Sun; Hui Zhang; Yibin Zhang; Weihua Zhou; Bin Zhang; Mridul Roy; Hong Liu; Mao Ye; Zi Wang; et al. (Elsevier, 2019)
Melanoma is a highly aggressive tumor with a poor prognosis, and half of all melanoma patients harbor BRAF mutations. A BRAF inhibitor, vemurafenib (PLX4032), has been approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) to treat advanced melanoma patients with BRAFV600E mutation. However, the efficacy of vemurafenib is impeded by adaptive resistance in almost all patients. In this study, using a cell-based SELEX (systematic evolution of ligands by exponential enrichment) strategy, we obtained a DNA aptamer (named LL4) with high affinity and specificity against vemurafenib-resistant melanoma cells. Optimized truncated form (LL4A) specifically binds to vemurafenib-resistant melanoma cells with dissociation constants in the nanomolar range and with excellent stability and low toxicity. Meanwhile, fluorescence imaging confirmed that LL4A significantly accumulated in tumors formed by vemurafenib-resistant melanoma cells, but not in control tumors formed by their corresponding parental cells in vivo. Further, a transmembrane protein CD63 was identified as the binding target of aptamer LL4A using a pull-down assay combined with the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. CD63 formed a supramolecular complex with TIMP1 and β1-integrin, activated the nuclear factor кB (NF-кB) and mitogen-activated protein kinase (MAPK) signaling pathways, and contributed to vemurafenib resistance. Potentially, the aptamer LL4A may be used diagnostically and therapeutically in humans to treat targeted vemurafenib-resistant melanoma. Keywords: melanoma, vemurafenib-resistant, aptamer, LL4A, CD63